Development Of A Basic Chemistry E-Book Enhanced With Multiple Representations And STEM Activities - Susanti, Laily Yunita; Fadilah, Rizka Elan; Khirzin , Muhammad Habbib; Hasanah, Rafiatul (Koordinat Jurnal MIPA, 2025)
Chemistry concepts are generally abstract so they require teaching materials that visualize those abstract concepts. The aims of this study were to develop a Basic Chemistry E-Book enhanced with multiple representations and a STEM approach. This study used a research and development model modified from the ADDIE model which consists of 5 stages, namely: (1) Analysis (analysis of students’ characteristics and course objectives), (2) Design (design of e-book and research instruments), (3) Develop (e-book production), (4) Implementation (expert judgement and field trials), and (5) Evaluation (the effectiveness test and revision of e-book). Research result showed that the feasibility of e-book based on the expert judgement got 93.75% as a score on the material feasibility component, 100% as a score of feasibility component and 95.40% as a score of the language and STEM component. Furthermore, the results of small-scale field trials obtained a percentage of 86% and large-scale field trials obtained a percentage of 87%. The effectiveness test of e-book got score 0,643 means e-book was effective enough for using in learning chemistry. Based on this study, e-book for Basic Chemistry Course based on multiple representations with the STEM approach is appropriate for being used in general chemistry course